Oral labetalol or alpha-methyldopa in the treatment of severe hypertension in preeclamptic patients - Morales-Avendaño, Verónica (2018)
Objective: To compare the efficacy of oral labetalol with oral alpha-methyldopa in the treatment of severe hypertension in preeclamptic patients. Design: Casecontrol study. Institution: Hospital Central “Dr. Urquinaona”, Maracaibo, Venezuela. Participants: 200 preeclamptic patients who were randomly assigned to be treated with oral labetalol (group A) or with oral alpha-methyldopa (group B). Main outcome measures: Hypertension treatment efficacy, rate of persistence of hypertension and adverse effects related to drug use. Results: There were no differences between groups regarding maternal age, gestational age at the time of inclusion, and body mass index (p = ns). There were also no statistically significant differences in systolic, diastolic and mean arterial pressure between groups (p = ns). We observed that patients treated with oral labetalol had significantly lower values of systolic, diastolic and mean arterial pressure compared to patients treated with oral alphamethyldopa (p < 0.0001). No patient in group A had persistent hypertension, while 17 patients in group B did present it (p < 0.0001). The most common symptom in group A was headaches; in group B, nausea was significantly more frequent (p = 0.006). Conclusion: Oral labetalol is more effective than alpha-methyldopa in the treatment of severe hypertension in preeclamptic patients.